TEACHERS PERFORMANCE ANALYSIS OF VOCATION HIGH SCHOOL IN BANTEN PROVINCE - S, Mathodah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
This study aimed to analyze and prove the influence of leadership, school culture and competence on work motivation and its implication toward teacher?s performance of vocation high school at Banten province, both partially and simultaneously. The method used in this research were descriptive, survey and explanatory method with population size of 617 and sample size of 215 respondents. The method used to analysis data was SEM (Structural Equation Modeling). The research result, obtained the findings as follows: The leadership, school culture and competence both partially and simultaneously had positive and significant impact on work motivation with contribution (R2) 50%. Partially leadership dominantly influence on work motivation. Further on Structural 2 showed those: The leadership, school culture, competence and work motivation both partially and simultaneously had positive and significant impact on teacher?s performance with contribution (R2) 77%. Viewed as partial, the leadership had dominantly toward teacher?s performance. Concerning on direct and indirect effect that work motivation was being full mediating. This study found and recommended that to increase teacher?s  performance of vocation high school at Banten province needed to be extending work motivation, reflected by the dimension of affiliation and supported with an increase in leadership which reflected by the dimension of personality especially integrity, and then backed with an enhance in teacher?s competence which reflected by the dimension of personality, especially hold the norms, and the last one repaired the school culture with the dimension bureaucracy especially coordination